The influence of in-service professional development on saudi efl teachers’ professional identity - Hussain, Ahmad (2021)
Teacher professional identity has a powerful influence on teachers’ classroom practices, student learning outcomes, and other academic roles and responsibilities. Although teacher professional identity is related to professional development, most professional development initiatives focus on developing teaching knowledge and skills rather than enhancing teacher professional identity. The current study investigates the influence of Cambridge English Teacher (CET) professional development on professional identity and pedagogical practices of EFL teachers in an English Language Institute at a Saudi Arabian public university. Utilizing a convergent parallel mixed-methods design, quantitative questionnaire, semi-structured interview protocol and open-ended questionnaire provide data to understand EFL teachers’ identity development as they participate in the CET development program. Based on the theoretical framework of the current study, EFL teacher identity change concerning professional development is characterized by five identity attributes: teaching context, teacher collaboration, classroom practices, teacher self-efficacy (TSE), and teacher agency. In analyzing the PRE and POST data, descriptive statistics and Wilcoxon signed Rank test were employed. The findings show that all five teacher identity attributes are significantly influenced as a result of the CET development program. However, regarding the extent to which teacher identity attributes enhanced, the results exhibit different degrees of change. The qualitative data reveal that the CET program’s participants enhance their knowledge and understanding of the unique Saudi EFL context at several levels. It is also found that the CET development program fosters teacher collaboration among the ELI faculty members in various ways. Next, the participants indicate that they have co-constructed a repertoire of classroom beliefs and practice, in addition to enhancing their learner-centred pedagogical practices. Also, the CET program’s participants nurture their teacher self-efficacy beliefs because of learning from each other and the trainers. Finally, participants’ teacher agency in various vistas of their profession was enhanced. The findings suggest that institutionally imposed professional development is useful for the development of teachers’ professional identity and their pedagogical practices, provided PD initiatives are cognizant of teachers needs and institutional requirements. The findings of the current study have implications for EFL teachers, teacher trainers or professional development specialists, and language institutes’ administration.